Optimalisasi Co-Working Space pada Kalangan Milenial Muslim di Surabaya - Azyraf Luhung, Padhmanabha Hyang; Cahyono, Hendry (Universitas Negeri Surabaya, 2020)
This study aims to see the convenience created by the koridor co-working space to visitors and startups. Co-working space is a place to accommodate the creative power of freelancers, startups, students, and also the community. Co-working space is part of the creative industry. Comfort becomes an important point when someone does his job. Sharia tourism makes the spatial space (co-working space) convenient for Muslims who use it, by facilitating with places of worship and selling halal food. The method used is a qualitative method using domain analysis techniques. The results of this study indicate that the koridor co-working space provides satisfying comfort for millennial Muslims in Surabaya.